Knowledge and Awareness of Obstructive Sleep Apnea and Its Related Complications Among Patients Visiting Outpatient Departments in a Tertiary Care Center: A Cross-Sectional Study - Adarsh Babu,Dr Prem Kumar Battina,Dr Dishan Y,Dr Ani Mol Iyyankutty,Dr Ananya S W (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Obstructive Sleep Apnea (OSA) is a common but often underdiagnosed sleep disorder with serioushealth implications, including cardiovascular disease, metabolic disorders, and neurocognitiveimpairment. Despite its high prevalence, public knowledge and awareness remain poor in mostpopulations.